Wnt activity and basal niche position sensitize intestinal stem and progenitor cells to DNA damage. (21st January 2015) - Tao, Si; Tang, Duozhuang; Morita, Yohei; Sperka, Tobias; Omrani, Omid; Lechel, André; Sakk, Vadim; Kraus, Johann; Kestler, Hans A; Kühl, Michael; Rudolph, Karl Lenhard
Abstract Aging and carcinogenesis coincide with the accumulation of DNA damage and mutations in stem and progenitor cells. Molecular mechanisms that influence responses of stem and progenitor cells to DNA damage remain to be delineated. Here, we show that niche positioning and Wnt signaling activity modulate the sensitivity of intestinal stem and progenitor cells (ISPCs) to DNA damage. ISPCs at the crypt bottom with high Wnt/β‐catenin activity are more sensitive to DNA damage compared to ISPCs in position 4 with low Wnt activity. These differences are not induced by differences in cell cycle activity but relate to DNA damage‐dependent activation of Wnt signaling, which in turn amplifies DNA damage checkpoint activation. The study shows that instructed enhancement of Wnt signaling increases radio‐sensitivity of ISPCs, while inhibition of Wnt signaling decreases it. These results provide a proof of concept that cell intrinsic levels of Wnt signaling modulate the sensitivity of ISPCs to DNA damage and heterogeneity in Wnt activation in the stem cell niche contributes to the selection of ISPCs in the context of DNA damage.